The MLL partial tandem duplication: evidence for recessive gain-of-function in acute myeloid leukemia identifies a novel patient subgroup for molecular-targeted therapy - Whitman, Susan P. (© 2005 by The American Society of Hematology, 2005)
MLL (ALL-1) chimeric fusions and MLL partial tandem duplications (PTD) may have mechanistically distinct contributions to leukemogenesis. Acute myeloid leukemia (AML) blasts with the t(9;11)(p22; q23) express MLL-AF9 and MLL wild-type (WT) transcripts, while normal karyotype AML blasts with the MLL(PTD/WT) genotype express MLL PTD but not the MLL WT. Silencing of MLL WT in MLL(PTD/WT) blasts was reversed by DNA methyltransferase (DNMT) and histone deacetylase (HDAC) inhibitors, and MLL WT induction was associated with selective sensitivity to cell death. Reduction of MLL PTD expression induced MLL WT and reduced blast colony-forming units, supporting opposing functions for MLL PTD and MLL WT whereby the MLL PTD contributes to the leukemic phenotype via a recessive gain-of-function. The coincident suppression of the MLL WT allele with the expression of the MLL PTD allele, along with the functional data presented here, supports the hypothesis that loss of WT MLL function via monoallelic repression contributes to the leukemic phenotype by the remaining mutant allele. These data from primary AML and the pharmacologic reversal of MLL WT silencing associated with a favorable alteration in the threshold for apoptosis suggest that these patients with poor prognosis may benefit from demethylating or histone deacetylase inhibitor therapy, or both.